Booklet titled 'The Case for Ireland Re-stated, To the President of the United States of America, on Independence Day, 1918', by Crawford Hartnell, Dublin, 1918, - Hartnell, Crawford. (1918)
Subtitled 'With a series of illustrated historical points supplementing the text'. Includes copy Declaration of Independence. Drawn up at Mansion House Conference for "Irish Political and Labour Organizations", 18 April 1918.